The Maine Farmers' Almanac, For the Year of Our Lord 1836; Being Bissentile or Leap Year, and the sixtieth - sixty-first of our Country's Independence. - Robinson, Daniel, 1777-1866. (Tufts University. Tisch Library., 2018)
24 leaves. Tisch Library copy contains handwritten annotations.